Nonoxid-HMGB1 Attenuates Cognitive Impairment After Traumatic Brain Injury in Rats - Chen, Jun-Quan; Gao, Shuang-Qi; Luo, Lun; Jiang, Zong-Yuan; Liang, Chao-Feng; He, Hai-Yong; Guo, Ying (Frontiers in Medicine, 2022)
Traumatic brain injury (TBI) is a major global burden of health. As an accepted inflammatory mediator, high mobility group box 1 (HMGB1) is found to be effective in facilitating neurogenesis and axonal regeneration. SH3RF2 (also known as POSHER), an E3 ligase SH3 domain-containing ring finger 2, belongs to the SH3RF family of proteins. Here, we aimed to investigate the role of redox states of HMGB1 on neurite outgrowth and regeneration both in vitro and in vivo. In this study, distinct recombinant HMGB1 redox isoforms were used. Sequencing for RNA-seq and data analysis were performed to find the potential downstream target of nonoxid-HMGB1 (3S-HMGB1). Protein changes and distribution of SH3RF2 were evaluated by western blot assays and immunofluorescence. Lentivirus and adeno-associated virus were used to regulate the expression of genes. Nonoxid-HMGB1-enriched exosomes were constructed and used to treat TBI rats. Neurological function was evaluated by OF test and NOR test. Results demonstrated that nonoxid-HMGB1 and fr-HMGB1, but not ds-HMGB1, promoted neurite outgrowth and axon elongation. RNA-seq and western blot assay indicated a significant increase of SH3RF2 in neurons after treated with nonoxid-HMGB1 or fr-HMGB1. Notably, the beneficial effects of nonoxid-HMGB1 were attenuated by downregulation of SH3RF2. Furthermore, nonoxid-HMGB1 ameliorated cognitive impairment in rats post-TBI via SH3RF2. Altogether, our experimental results suggest that one of the promoting neurite outgrowth and regeneration mechanisms of nonoxid-HMGB1 is mediated through the upregulated expression of SH3RF2. Nonoxid-HMGB1 is an attractive therapeutic candidate for the treatment of TBI.